Loss of TGF-β signaling in osteoblasts increases basic-FGF and promotes prostate cancer bone metastasis. (1st April 2018) - Meng, Xiangqi; Vander Ark, Alexandra; Daft, Paul; Woodford, Erica; Wang, Jie; Madaj, Zachary; Li, Xiaohong
Abstract: TGF-β plays a central role in prostate cancer (PCa) bone metastasis, and it is crucial to understand the bone cell–specific role of TGF-β signaling in this process. Thus, we used knockout (KO) mouse models having deletion of the Tgfbr2 gene specifically in osteoblasts ( Tgfbr2 Col1CreERT KO) or in osteoclasts ( Tgfbr2 LysMCre KO). We found that PCa-induced bone lesion development was promoted in the Tgfbr2 Col1CreERT KO mice, but was inhibited in the Tgfbr2 LysMCre KO mice, relative to their respective control Tgfbr2 FloxE2 littermates. Since metastatic PCa cells attach to osteoblasts when colonized in the bone microenvironment, we focused on the mechanistic studies using the Tgfbr2 Col1CreERT KO mouse model. We found that bFGF was upregulated in osteoblasts from PC3-injected tibiae of Tgfbr2 Col1CreERT KO mice and correlated with increased tumor cell proliferation, angiogenesis, amounts of cancer-associated fibroblasts and osteoclasts. In vitro studies showed that osteoblastogenesis was inhibited, osteoclastogenesis was stimulated, but PC3 viability was not affected, by bFGF treatments. Lastly, the increased PC3-induced bone lesions in Tgfbr2 Col1CreERT KO mice were significantly attenuated by blocking bFGF using neutralizing antibody, suggesting bFGF is a promising target inhibiting bone metastasis. Highlights: TGF-β signaling in osteoblasts inhibits, but in osteoclasts promotes, bone metastasis. bFGF mediates the effect of loss of TGF-β signaling in osteoblasts. bFGF increases osteoclastogenesis, but inhibits osteoblastogenesis. bFGF had no direct effect on PC3 cell viability. bFGF is a promising target for inhibiting bone metastasis.